Examination of the Interaction between Parental Military-Status and Race among Non-Hispanic Black and Non-Hispanic White Adolescents with Overweight/Obesity. (3rd March 2022) - Higgins Neyland, M K; Shank, Lisa M; Lavender, Jason M; Burke, Natasha L; Rice, Alexander; Gallagher-Teske, Julia; Markos, Bethelhem; Faulkner, Loie M; Djan, Kweku G; Kwarteng, Esther A; LeMay-Russell, Sarah; Parker, Megan N; et al.
Abstract: Objectives: Adolescent military-dependents experience distinct risk and protective factors, which may necessitate additional clinical considerations. In civilian youth, overweight/obesity is associated with eating, internalizing, and externalizing difficulties, with some studies reporting more difficulties among non-Hispanic White (vs. non-Hispanic Black) youth. It is unknown if these disparities exist among adolescent military-dependents, or between civilian and military-dependent youth. Methods: Non-Hispanic Black (187 civilian, 38 military-dependent) and non-Hispanic White (205 civilian, 84 military-dependent) adolescents with overweight/obesity (14.7 ± 1.6 years; 73.9% girls; body mass index adjusted for age and sex 1.9 ± 0.5) completed a disordered-eating interview; parents completed a measure assessing their child's internalizing and externalizing difficulties. Multiple linear regressions examined parental military-status as a moderator of the relationship of participant race with eating, internalizing, and externalizing difficulties. Results:     White civilian youth with overweight/obesity reported significantly greater disordered-eating than their Black peers ( p < .001); there were no other significant racial differences. In all regressions, parental military-status significantly moderated the association between race and each dependent variable ( p s < .047). Black military-dependents (vs. civilians) reported more disordered-eating and internalizing difficulties ( p s = .01). White military-dependents (vs. civilians) reported fewer externalizing difficulties ( p = .01). Conclusions:     Black adolescent military-dependents with overweight/obesity may experience more eating and internalizing difficulties (vs. civilians), a pattern not observed among White participants. Future work should examine if being a military-dependent and a historically marginalized racial group member accounts for these findings. Such data may inform providers of youth with intersecting minority identities.